Socio-economic Impact Analysis of Contract Farming of Gherkin in Karnataka - H.D, Venu Prasad; Singh, Premlata; Chaturvedi, V.K. (Indian Journal of Extension Education, 2012)
Gherkin (Cucumis anguria L.) is an export-oriented vegetable (cucurbit) crop. Karnataka state accounts for almost 90 per cent of export of preserved gherkins. Its cultivation is largely driven through contract farming. The present study was undertaken with the specific objectives of (i) to analyze the socioeconomic impact of contract farming of gherkin on farmers and (ii) to study the perceptions of farmers about the socio-economic implications of contract farming of gherkin. The study was carried out in two randomly selected talukas, viz. 'Kunigal' and 'Sira' of purposively selected 'Tumkur' district of Karnataka state. The total sample size comprising 60 respondents (30 from each of the two selected taluka) who were drawn randomly from the list of gherkin contract farmers, provided by contracting companies, namely Global Green Contracting company and 'Reitzil' company. The socioeconomic impact was determined in terms of six broad aspects of consequences and socio-economic implications were explored on the basis of eight dimensions of change indicators. The data was collected through a pre-tested structured interview schedule. The overall analysis of socio-economic impact revealed that with the participation in gherkin contract farming, the farmers were able to improve their standard of living and status in the society.Alarge majority of respondents (81.70 %) reported about diversification of cropping system more than half, (53.30 %) of the respondents were able to repay their pending loans. All the respondents felt that gherkin contract farming provided employment opportunities to a large extent and thereby helps to check out migration/displacement. The finding emanating from study makes a strong case for promoting the model of contract farming of gherkin on a wider scale.
Keywords: Contract farming; Gherkin; Impact analysis; Socio-economic implications